Elevated neutrophil-to-lymphocyte ratio in the diagnosis of subacute thyroiditis - Kilinc, Faruk; Ergun, Yakup; Pekkolay, Zafer; Tuzcu, Sadiye Altun; Gozel, Nevzat; Tuna, Mazhar Muslum; Tuzcu, Alpaslan Kemal (Mattioli 1885, 2018)
Subacute thyroiditis (SAT) is a self-limiting inflammatory condition of the thyroid gland in which multinucleated giant cells constitute a key histological finding. The neutrophil-lymphocyte ratio (NLR), determined from peripheral blood, is accepted as an available and practical indicator of the systemic inflammation. The purpose of this study was to determine the neutrophil-to-lymphocyte ratio (NLR), a novel marker of inflammation, in patients with SAT and to compare these values with those from healthy subjects. A total of 150 participants were included in the study, 75 SAT patients and 75 healthy volunteers. Retrospectively, demographic and laboratory data of the subjects were obtained from our institution's database. Patients with active infection, diabetes mellitus, malignancy, other chronic inflammatory diseases and hematologic disorders were excluded from the study. Values for complete blood count (CBC) and serum laboratory parameters of SAT patients were the baseline values obtained at the time of SAT diagnosis. Control subjects consisted of healthy volunteers who visited our institution for a routine check-up. A total of 75 subacute thyroiditis patients 54 (72%) were female and 21 (28%) were males and 50 (66.6%) were female and 25 (33.3%) were male and 75 were healthy adults were included. The mean age was 39.95 +/- 14.2, years for patients with SAT and 37.53 +/- 13.45 years for the control group. There was no significant difference between the age for groups (P = 0.13). NLR levels were found to be 3,56 +/- 2,64 in patients with SAT; NLR levels were found to be 1.41 +/- 0.9 in the control group. NLR levels were significantly higher in patients with SAT compared to the control group. Our study showed that increased NLR may be useful as an indicator of the presence of SAT, especially in complicated cases. The assessment of neutrophil-lymphocyte ratio in conjunction with radiological and clinical findings will assist in the achievement of an accurate diagnosis. Larger, prospective studies are required to determine its usefulness in assessing diagnostic potential and treatment outcomes in SAT patients.
Keywords: Subacute thyroiditis; neutrophil-to-lymphocyte ratio; diagnosis